Enhanced photovoltaic performance of perovskite solar cells by Co-doped spinel nickel cobaltite hole transporting layer - Ioakeimidis, Apostolos; Papadas, Ioannis T.; Tsikritzis, Dimitris; Armatas, Gerasimos S.; Kennou, Stella; Choulis, Stelios A. (My University, 2019)
A solution combustion synthesized hole transport layer (HTL) of spinel nickel cobaltite (NiCo 2 O 4 ) incorporating 3% Cu-2% Li was fabricated using the doctor-blading technique for planar inverted perovskite solar cells (PVSCs). PVSCs incorporating 3% Cu-2% Li-doped NiCo 2 O 4 showed an increase in Jsc and Voc device performance parameters compared to unmodified NiCo 2 O 4 , leading to power conversion efficiency (PCE) of 16.5%. X-ray photoelectron spectroscopy measurements revealed the tendency of Cu cations to replace preferably the surface Ni atoms by changing the surface stoichiometry of NiCo 2 O 4 , inducing a cathodic polarization. Ultraviolet photoelectron spectroscopy measurements unveiled the increase in the ionization potential by 0.1 eV for a co-doped NiCo 2 O 4 film compared to unmodified NiCo 2 O 4 -based HTL. We attribute the enhanced PCE of the inverted PVSCs presented to the improved hole extraction properties of 3% Cu-2% Li NiCo 2 O 4 HTL.
Keywords: Hole extractions; Hole transport layers; Photovoltaic performance; Solution combustion; Power conversion efficiencies